2017
DOI: 10.1001/jama.2017.17535
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging New Uses for Old Drugs

Abstract: US Food and Drug Administration (FDA) approval of a new drug typically coincides with a period of patent protection, during which the manufacturer will often apply for additional indications to expand the market for the product. For example, the tyrosine kinase inhibitor imatinib (Gleevec; Novartis) was originally approved to treat Philadelphia chromosomepositive chronic myelogenous leukemia, but has since been approved for treatment of other cancers. Many noncancer drugs also follow this pattern, including bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…Pharmaceutical companies often choose not to invest in new therapeutic indications after expiry of basic patent and regulatory protection periods of their approved products (Langedijk et al, 2016;Nayroles et al, 2017). Patent claims for secondary uses often offer weaker protection compared to the primary basic product patent claims so the risk of free-riding by competitors is high (Sachs et al, 2017). Developing a new indication outside of a company's therapeutic focus is also high-risk and costly (Novac, 2013;Pushpakom et al, 2019).…”
Section: Challenges In Bringing New Uses On-labelmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmaceutical companies often choose not to invest in new therapeutic indications after expiry of basic patent and regulatory protection periods of their approved products (Langedijk et al, 2016;Nayroles et al, 2017). Patent claims for secondary uses often offer weaker protection compared to the primary basic product patent claims so the risk of free-riding by competitors is high (Sachs et al, 2017). Developing a new indication outside of a company's therapeutic focus is also high-risk and costly (Novac, 2013;Pushpakom et al, 2019).…”
Section: Challenges In Bringing New Uses On-labelmentioning
confidence: 99%
“…Developing a new indication outside of a company's therapeutic focus is also high-risk and costly (Novac, 2013;Pushpakom et al, 2019). Instead, companies may actually benefit from off-label prescribing of their products because it expands the patient population without them having to apply for a variation or extension of the marketing authorization (Sachs et al, 2017; STAMP European Commission expert group, 2017a). In addition, research has shown that the evidence base supporting new uses for marketed, off-patent medicines in anticancer treatment is largely built through academic or independent research .…”
Section: Challenges In Bringing New Uses On-labelmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding new uses outside the scope of the original medical indication for existing drugs, referred to as drug repurposing or repositioning, is one solution to achieve efficiency. Existing drugs have already been tested in humans, have been demonstrated an acceptable level of safety and tolerability, and are often approved by regulatory agencies for human use (Sachs, et al, 2017). This could potentially increase the success rate of drug development and reduce the cost in terms of time.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of long-term, real-world data with established safety records provides us with an opportunity to use generic drugs to improve health outcomes in new indications at a lower cost. 1 However, there exist inherent limitations, such as unmeasured confounders, in the use of real-world data. New strategies to validate the potential use of old drugs in addition to existing big data are warranted.…”
Section: Introductionmentioning
confidence: 99%